Investigation of Microbiota Alterations and Intestinal Inflammation Post-Spinal Cord Injury in Rat Model - O'Connor, Gregory; Jeffrey, Elisabeth; Madorma, Derik; Marcillo, Alexander; Abreu, Maria T.; Deo, Sapna K.; Dietrich, W. Dalton; Daunert, Sylvia (Journal of neurotrauma, 2018)
Although there has been a significant amount of research focused on the pathophysiology of spinal cord injury (SCI), there is limited information on the consequences of SCI on remote organs. SCI can produce significant effects on a variety of organ systems, including the gastrointestinal tract. Patients with SCI often suffer from severe, debilitating bowel dysfunction in addition to their physical disabilities, which is of major concern for these individuals because of the adverse impact on their quality of life. Herein, we report on our investigation into the effects of SCI and subsequent antibiotic treatment on the intestinal tissue and microbiota. For that, we used a thoracic SCI rat model and investigated changes to the microbiota, proinflammatory cytokine levels, and bacterial communication molecule levels post-injury and gentamicin treatment for 7 days. We discovered significant changes, the most interesting being the differences in the gut microbiota beta diversity of 8-week SCI animals compared to control animals at the family, genus, and species level. Specifically, 35 operational taxonomic units were enriched in the SCI animal group and three were identified at species level; Lactobacillus intestinalis, Clostridium disporicum, and Bifidobacterium choerinum. In contrast, Clostridium saccharogumia was identified as depleted in the SCI animal group. Proinflammatory cytokines interleukin (IL)-12, macrophage inflammatory protein-2 (MIP-2), and tumor necrosis factor alpha were found to be significantly elevated in intestinal tissue homogenate 4 weeks post-SCI compared to 8-weeks post-injury. Further, levels of IL-1β, IL-12, and MIP-2 significantly correlated with changes in beta diversity 8-weeks post-SCI. Our data provide a greater understanding of the early effects of SCI on the microbiota and gastrointestinal tract, highlighting the need for further investigation to elucidate the mechanism underlying these effects.